IMPLEMENTASI GMP UNTUK MENINGKATKAN MUTU DAN KEAMANAN GULA SEMUT: PELATIHAN DAN PENDAMPINGAN PADA KELOMPOK TANI NIRA SARI MURNI, CILONGOK - Nur Wijayanti; Laksmi Putri Ayuningtyas; Nofiyati Nofiyati (Universitas Mataram, 2025)
Local commodity-based food MSMEs such as palm sugar have great potential to boost the village economy. However, the main challenges faced are product quality and food safety aspects that do not yet fully meet standards. This community service activity aims to increase the knowledge and understanding of members of the Nira Sari Murni Farmer Group regarding the application of Good Manufacturing Practices (GMP) in palm sugar production. The methods used were socialization, training, and pre-test and post-test evaluations. A total of 30 participants took part in this activity. The evaluation results showed a significant increase in participants' understanding. In the pre-test, misperceptions regarding the storage of palm sugar and the dangers of consuming moldy palm sugar were still found (18.2% answered incorrectly). However, in the post-test, all participants (100%) answered all questions correctly. This shows that the training was effective in raising awareness of the importance of GMP in palm sugar production. The implementation of GMP is expected to improve product quality, food safety, and the competitiveness of palm sugar MSMEs in local and global markets. Before the mentoring, this group's palm sugar production process was rudimentary and did not fully comply with GMP standards. After mentoring on GMP implementation, several significant positive changes occurred.